Investigating personnel perceptions of leadership styles during WFH within private higher education in South Africa - Bisschoff, Christo; Cassim, Nadeem; Botha, Christoff; Botha, Doret (Journal of Economic Development, Environment and People, 2024)
The Covid-19 pandemic has transformed the nature of work, with the implementation of the Work from Home (WFH) arrangement. This change has implied a series of considerations for business operations, including leadership. The purpose of this study is to ascertain academic personnels’ view on the leadership received during the WFH period, with the intention of assessing the leadership styles used, as well as measuring the achievement of the outcomes of leadership. The study was conducted within private higher education in South Africa. Whilst there are studies that assess the leadership styles during the WFH period, no study could be located that assesses this phenomenon within higher education, as well as private higher education in South Africa, to be specific. The study utilised a quantitative research methodology with cross-sectional design and a positivist research paradigm. The target population included all academic personnel within the private higher education institution under study (i.e., 133 personnel). Total population sampling was utilised, and data was collected through an online administered survey utilising the Multifactor Leadership Questionnaire (MLQ), comprising of 46 items. Eleven items were also included to ascertain the demographic details of participants. The study utilised descriptive, inferential and multivariate analysis techniques. A response rate of 79% was achieved. The findings of this study suggested that academic personnel held a general positive sentiment of the leadership approaches used by seniors during the WFH period. Transformational leadership was found to be the dominant approach utilised, as was found, through the correlation with literature, to be the suitable approach used during WFH. In addition, the study found a general level of comfort amongst staff regarding the achievement of the outcomes of leadership. Although there was an overall positive sentiment held regarding leadership during WFH, primary results also suggest areas for improvement, particularly on the increase in the use of transformational leadership and avoidance of instances of passive avoidance leadership. Considering that WFH has been identified as a viable solution for the foreseeable future, private higher education in South Africa should give due consideration to the leadership suggestions recommended in this study, to ensure that leadership approaches are conducive to WFH. This study contributes to literature surrounding the concept of leadership within the WFH period, within private higher education.